Human Trafficking In The Perspective Of Islam And Feminism And Its Prevention Efforts In Indonesia - Farida, Umma; Istianah, Istianah; Kasdi, Abdurrohman (UIN Sunan Kudus, 2024)
This paper describes human trafficking according to the Islamic and feminist approaches and efforts to prevent it in Indonesia. Human trafficking is an organized crime, latent and hidden, so it is difficult to overcome. Based on data from the United Nations (UN), cases of trafficking in Indonesia continue to increase. The victims are women and minors. This article aims to explain human trafficking by examining Islamic texts and feminism and its prevention efforts in Indonesia using descriptive-analytical research methods. The collected data is then analyzed using Islamic and feminist approaches. The findings show that both approaches emphasize that human trafficking is a crime against humanity. It destroys and robs freedom and humanity. So, the act of trafficking is tyranny and unlawful because it is contrary to the mission of Quranic and prophetic teachings. Besides, the feminist approach argues that prostitution, human trafficking, and sex trafficking must be stopped and assumes that the elimination of prostitution will end the need for sex trafficking and that the promotion of gender equality can more generally take place. Crucial to prevention is not only protecting and empowering people who are victims of trafficking but also considering the implications of how the trafficking victims are forced to become productive subjects. Considering that this trafficking crime has been organized across countries, the prevention efforts need to be carried out comprehensively by involving various government, private, and NGO sectors, international agencies, community organizations, and the mass media. Equally important is the role of religion in involving non-governmental organizations (NGOs) and community organizations.